The value of 18F-fluorodeoxyglucose PET (18F-FDG PET) and MRI spectroscopy in underpinning suspicious breast cancer - Shaharuddin, Shazreen; Shakher, Ramdave; Abdullah Suhaimi, Shahrun Niza; Ahmad Saad, Fathinul Fikri (Universiti Putra Malaysia Press, 2018)
The aim of this study was to evaluate the value of MRI spectroscopy and association with the altered glucose metabolism on 18-FDG PET/CT in patients with suspicious breast cancer. Eight selected breast cancer patients with BIRADS 4 or 5 on mammogram were recruited and patients underwent 18F-FDG PET/CT MRI (spectroscopy). The standardise uptake value (SUVmax) was analysed to determine the degree of the altered glucose metabolism on the PET. The metabolites of tumor lesions were measured using in vivo proton MR spectroscopy (MRS) of the breast. There were eight females with a mean age of 55.3±12.2 years with a biopsy result of invasive ductal carcinoma (2), lobular carcinoma (1) and benign lesion (5). There was a significant difference between the mean of the malignant tumour (SUVmax 4.28±3.74 g/ml) and the mean of the benign tumour (SUVmax: 2.33±0.9 g/ml). On the per-lesional basis of the MRS correlate with SUVmax, the suspicious breast tissue exhibited raised creatinine metabolites (mean: 3.39±0.54u) with significant correlation SUVmax mean 3.06±2.34 as compared to N-acetyl Aspartate (NAA), (mean: 2.84±0.99u) and choline (mean: 2.46± 0.70 u). This study showed that high SUVmax was associated with malignant cancer and the high creatinine metabolite that correlated with the SUVmax could potentially be utilised as a surrogate marker in detecting breast cancer.